An unexplained fetal intracranial hemorrhage with extensive and multifocal hemorrhagic lesions: A case report. Issue 25 (24th June 2022) - Gao, Baorong; Zhang, Li; Wei, Qiang
Abstract: Rationale: Fetal intracranial hemorrhage (ICH) is an extremely rare complication of pregnancy, with subsequent neurological sequelae or fetal death. The diagnosis of fetal ICH is primarily based on ultrasound or magnetic resonance imaging. Patient concerns: An asymptomatic woman at 31 weeks of gestation was referred for a detailed anomaly scan because routine fetal ultrasonography showed suspected fetal ICH. Diagnoses: Fetal ICH with extensive and multifocal hemorrhagic lesions was diagnosed by ultrasound and magnetic resonance imaging imaging and finally confirmed by postmortem examination. Interventions: The woman opted for pregnancy termination after medical consultation. Labor was induced by mifepristone and rivanol infusion. Outcomes: The patient delivered a stillborn male infant weighing 1522 g. We tried our best to screen the possible etiology contributing to fetal ICH; unfortunately, no evidence of obvious causes or predisposing factors was identified. Lessons: Medically unexplained massive fetal ICH may cause an unfavorable prognosis, and prompt termination of pregnancy is appropriate, although there is no consensus on the optimal mode of delivery.